A Greedy Policy for the Admission Control of Self-Similar Traffic - Melo, Cesar A. V.; Fonseca, Nelson L. S. (Journal of Communication and Information Systems, 2017)
Admission control is a fundamental mechanism for the provisionof Quality of Services in multiservice networks. The control of long-range dependent traffic demands specially designed mechanism. In tlus paper, a greedy policy for the admission control of self-similar traffic is introduced. This policy accepts flows into the network according to a decreasing order of revenue. It is shown that results produced by this new policy are close to the one produced by and optimum policy.